Trajectories of health‐related quality of life among renal transplant patients associated with graft failure and symptom distress: Analysis of the BENEFIT and BENEFIT‐EXT trials. Issue 6 (11th January 2020) - Purnajo, Intan; Beaumont, Jennifer L.; Polinsky, Martin; Alemao, Evo; Everly, Matthew J.
Abstract : Understanding the correlation between transplant symptoms, health‐related quality of life (HRQoL), and graft outcomes is needed to support patient‐focused drug development and posttransplant management. A post‐hoc analysis of patient‐reported outcomes from the Phase III belatacept trials was conducted in order to investigate the interrelationship between trajectories of HRQoL, symptom experience, and allograft outcomes. HRQoL and symptom experience were evaluated using Short‐Form 36 Survey (SF‐36) and Modified Transplant Symptom Occurrence and Distress Scale (MTSOSD‐59R), respectively. HRQoL was captured in 831 eligible renal transplant patients at baseline, 12, 24, and 36 months posttransplant. Following transplantation, patients reported improvements in all SF‐36 subscales compared to baseline. Latent class analysis revealed four trajectories in perceived general health, which were associated with graft failure after adjustment. Compared to patients with good perceived health, patients with fair and poor perceived health had 4.7 (95% confidence interval [CI] 1.5‐14.8, P < .01) and 19.8 (95% CI 5.9‐66.0, P < .01) times the risk of graft failure, respectively. Using multinomial logistic regression, different sets of symptoms were associated with perceived general health at baseline and 12 months posttransplant. The study supports monitoring HRQoL and symptom experience to capture each patient's health perspective, improve drug development, and optimize posttransplant management. Abstract : The perceived general health of renal transplant recipients follows several distinct longitudinal trajectories, identified via latent class mixed modeling, and these patterns are associated with symptom distress and risk of graft failure.